Volatilidade implícita das opções de ações: uma análise sobre a volatilidade futura - Mello, Arthur Ribeiro de Aquino Figueiredo (2009)
The purpose of this study is to examine the predictive power of the market about future volatility using the information obtained from the options on Petrobras and Vale. We will also compare the results with models such as GARCH and EWMA. Similar studies were performed in the U.S. stock market: Either with selected stocks or the S & P 100 Index, the results are not conclusive. Even if Canina and Figlewski (1993) find that the 'implied volatility has virtually no correlation with future volatility', Christensen and Prabhala (1998) conclude that implied volatility is a good predictor of future volatility. Andrade and Tabak (2001) use dollar options to study the information content power of the options on dollar. They also compare the predictive power of implied volatility withmodels such as EWMA or GARCH. The authors conclude that implied volatility is a biased estimator of future volatility but has a better performance compared with statistical models. Gabe and Portugal (2003) compare the implied volatility of options on Telemar (TNLP4) with statistical models like GARCH. In this case, implied volatility is also a biased estimator, but the statistical models were also good predictors and showed no bias. The data in this study are taken during 2008 and early 2009, using intraday observations of implied volatilities for the first two maturities of 'at the money' options on Petrobras and Vale. The observed implied volatility for both stocks contains relevant information about future olatility,similarly to previous studies, is biased. Specifically for Petrobras, GARCH model proved to be an efficient predictor of future volatility.